FAMILY COOPERATION AND MINORS’ BONDS WITH THE FAMILY IN RESIDENTIAL CARE PROGRAMS - Martín, Eduardo; Torbay Betancor, Ángela; Rodríguez Blanco, Teresa (Anales de Psicología / Annals of Psychology, 2008)
From an ecological approach, the work that is made with the families of the minors who live in residential care services receives a special interest. The primary target of this work is to analyze the evolution of the bonds of the minor with its family and the cooperation of this one with the residence. Taking two separated measures nine months in the time to a total of 138 cases, and using the scale of monthly observation of objectives of the Individualized Educative Project, we found three groups of evolution: improvement, maintenance and worsening. The variables of the case do not seem to influence in this evolution. Also, it is observed like, mainly the improvement of the cooperation of the family with the residence, repels positively in the autonomy of the minors and the adapta-tion to the residential context, not being relation with the adaptation to the school.